Bioinspired concise synthesis of caged Sesquiterpenoids Artatrovirenols A and B - Yunxia Yang; Dong Xie; Liang Huo; Yue Liu; Jinbo Duan; Huilin Li; Pan-Pan Zhou; Xingang Xie; Xuegong She (Nature Communications)
Abstract Artatrovirenols A and B are two newly isolated sesquiterpenoids with a complex caged framework. We report herein a concise synthesis of artatrovirenols A and B in 9 and 8 steps, respectively. The complex caged tetracycle is rapidly constructed from a known planar guaiane-type precursor through a bioinspired intramolecular [4 + 2] cyclization to firstly access artatrovirenol B, which is further transformed into artatrovirenol A through a biomimetic epoxidation-mediated lactonization reaction. This synthesis establishes a concise asymmetric approach to access artatrovirenols A and B, and also provides insightful evidence to their biogenetic pathway in nature.